Pengaruh Lingkungan Kerja Dan Kompensasi Finansial Terhadap Loyalitas Karyawan Melalui Motivasi Kerjavariabel Intervening Pada Pt. Gersindo Minang Plantation Pasaman Barat Sumatera Barat - Astika Mulia Sari; Seno Andri (Peneliti.net, 2023)
This study aims to determine the effect of work environment and financial compensation on employee loyalty through work motivation as an intervening variable. The sample in this study were 86 employees using stratified random sampling technique. The data obtained from the results of the questionnaire were then processed by statistical tests through the Smartpls application. The results of the study show that the work environment has no effect on employee loyalty, while financial compensation and work motivation have a positive and significant effect on employee loyalty. Work environment and financial compensation have a positive and significant effect on work motivation and work environment and work motivation have a positive and significant effect on employee loyalty through work motivation as an intervening variable.